Reframing the Study of Policy Implementation: Lived Experience as Politics. (January 2015) - Werts, Amanda Bell; Brewer, Curtis A.
This policy implementation study examines the experiences of four elementary school principals using photomethods. We employ Rancière and Merleau-Ponty's theorizations on democracy and making sense to understand the lived policy experiences of school principals and these individual's potential for practicing democratic politics. At its heart, implementation by local actors is a political undertaking. Our results indicate implementation is a spatially inhabited practice involving negotiation and strategy, where local actor's experiences moderate and appropriate policy. Thus, we point out that attention to these spatially inhabited practices requires a fundamental shift in the frameworks and methodologies deployed in the investigation of policy implementation.